The elusive quest for sustainable off-grid electrification: New evidence from Indonesia - Mike Duthie; Jörg Ankel-Peters; Carly Mphasa; Rashmi Bhat (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
High hopes are pinned to mini-grids for rural electrification, especially in remote and sparsely populated areas. This note presents new evidence from a large evaluation of a US Millennium Challenge Corporation investment into mini-grids in Indonesia. We find that, a few years after commissioning, many mini-grids in the program do not operate properly, corroborating older concerns about the sustainability of mini-grids and off-grid energy systems that have been voiced for several years. Operational costs are typically high and electricity demand low. Minigrid programs should take these structural challenges into account, and especially abstain from overly optimistic electricity demand projections.
Keywords: H54; O13; O21; Q48; 330; Energy access; sustainability; infrastructure; mini-grids